Identification and characterisation of citrus biodiversity: traditional and molecular approaches - Georgiou A. (Improvement of the citrus sector by the setting up of the common conservation strategies for the free exchange of healthy citrus genetic resources, 2001)
An account is given of the techniques used to identify genetic biodiversity in citrus by traditional and molecular means. Concerning the molecular approach, PCR and non-PCR methods are shortly described. The interests and limitations of these techniques are highlighted, thus suggesting the integration of several methods as the best approach for the identification of genetic biodiversity in citrus.